The Use of “English Fun Learning” Program to Teach Vocabulary - Bunga Kirana; Jade Jatuporn (Universitas Muhammadiyah Semarang, 2023)
English has turned into a significant language in the time of globalization. Vocabulary is one part of English which plays a significant part in figuring out perusing and communicating all thoughts in composed or spoken structure. The researcher tries to find the efficient solution for improving the good vocabulary skill by implementing the English Fun Learning. English Fun Learning is a basic method of learning English by combining several games in the activity. This activity is carried out to improve oral interaction in English through games that allow the development of communication, understanding, creativity, and can foster interest in speaking English. The target from this kind of analysis is the students at SD N 02 Plelen. The implemented method in this research is qualitative. As per the end of analysis from this research, students' understanding increased after being taught using English Fun Learning with various learning techniques such as storytelling, media games, and spelling bees. This activity has relevance to the needs of students at school. Interesting English teaching media and learning methods will motivate students to be involved in English speaking activities.